Current and future threats for ecological quality management of South American freshwater ecosystems. Issue 2 (3rd April 2021) - Torremorell, Ana; Hegoburu, Cecilia; Brandimarte, Ana Lucia; Rodrigues, Eduardo Henrique Costa; Pompêo, Marcelo; da Silva, Sheila Cardoso; Moschini-Carlos, Viviane; Caputo, Luciano; Fierro, Pablo; Mojica, José Iván; Matta, Ángela Lucia Pantoja; Donato, Jhon Charles; et al.
ABSTRACT: Global change drivers including eutrophication, hydrological disturbance, climate change, chemical pollution, overexploitation, invasive species, and land-use change are affecting the function and structure of freshwater ecosystems. South American freshwater ecosystems are especially threatened by the combination of rising human pressures on natural resources (i.e., water use, intensive agriculture, mining, deforestation, and afforestation) and the lack of adequate legislation and economic resources for environmental protection and restoration. We assess the state of freshwater ecosystems in Argentina, Brazil, Chile, Colombia, Ecuador, Uruguay, and Venezuela, focusing on broad categories of human-induced threats grouped into 5 categories: climate change, watershed stressors, hydrological alteration, channel modification, and biological stressors. For most countries, the most severe threats are related to land uses such as mining, agriculture, and urban expansion. Other threats relate to the abstraction or wasteful use of water and the intense regulation of flows, including the effects of large hydraulic infrastructure. There is also an increasing need to empower public organisations that focus on environmental protection, to update or develop an adequate regulatory and legal framework, to provide adequate funding for the implementation of environmental legislation, and not least to implement ecological rehabilitation. Implementation of these steps would reduce the threats to South American aquatic ecosystems and allow progress toward the sustainable development of this region in future decades.